Unilateral Mandibular Torus in a Hypertensive and Alcoholic Patient: A Case Report - Guimarães Sampaio Trajano Dos Santos, Pedro; Negromonte Azevedo, Alice; Borges Araújo, Mariana; Mendonça de Oliveira, Jessika; Laís Melo de Lima Castro, Laís; Coutinho de Queiroz, Priscila Paulina; de Queiroz Marques Filho, Eudoro; Coelho Travassos, Rosana Maria; de Melo Almeida Fonseca, Felipe Leonardo; Barreto Silva, Luciano (Brazilian Journal of Implantology and Health Sciences, 2024)
Objective: The objective of this case report is to report a case of unilateral mandibular torus in an adult patient with hypertension and alcoholism, highlighting the clinical characteristics, diagnosis, and management. Methodology: In the literature review, to obtain scientific articles, the main reference sources in articles, dissertations and abstracts published in congresses were searched in the databases, using the main portals in the health area such as PubMed, Scielo and Google Scholar, using the terms: Mandibular Torus, Dentistry, Surgery, in Portuguese and English as search words. After collecting the abstracts, the relevant articles were collected in full, read and used in the present study. The case report describes the clinical maneuvers performed on a 58-year-old male patient, hypertensive and alcoholic. Conclusion: Unilateral mandibular torus is a rare condition that is usually asymptomatic and can be managed conservatively. Correct diagnosis is essential to differentiate this condition from pathological lesions and avoid unnecessary interventions. This case highlights the importance of clinical examination and differential diagnosis of mandibular torus in patients with systemic risk factors, such as hypertension and alcoholism. Surgical management was sufficient in this case, but periodic follow-up is essential to monitor changes and prevent complications.